A Rare Case of Infantile Myofibromatosis With Intra Cranial Involvement - Fatima Zahrae El Mansoury MD; Zakia El Yousfi MD; Ayman El Farouki MD; Siham El Haddad MD, PhD; Nazik Allali MD, PhD; Latifa Chat MD, PhD (SAGE Publishing, 2024)
Infantile myofibromatosis is a proliferative disorder occurring during infancy and early childhood, marked by the development of nodular or diffuse lesions consisting of various mesenchymal elements. Intracranial involvement is infrequently reported. Here, we present the case of a 3-year-old girl exhibiting a rare manifestation of IM with intracranial parenchymal involvement, displaying a histological pattern documented in existing literature on patients with infantile myofibromatosis. Subsequent MRI follow-up revealed no signs of recurrence.